Nanostructured Anode Materials for Lithium Ion Batteries: Progress, Challenge and Perspective. Issue 17 (27th June 2016) - Mahmood, Nasir; Tang, Tianyu; Hou, Yanglong
Abstract : Lithium ion batteries (LIBs) possess energy densities higher than those of the conventional batteries, but their lower power densities and poor cycling lives are critical challenges for their applications to electric vehicles (EVs) or grid stations. The energy and power densities, as well as the life of LIBs are dependent on electrodes where sluggish diffusion control process and structural stability are the main concerns. Here, the lithium storage mechanism of anode materials and the Goodenough diagram to explain the potential of cell and key parameters to determine the performance of an anode are highlighted. The cost reduction parameters and the availability of anode materials for future batteries on the basis of their resources and performances will be discussed. Further, the recent progress on anode nanostructures and solutions to the associated challenges will be outlined. The use of several techniques to determine the dynamic variations in nanostructures including both structural and chemical changes of electrode nanostructures during cycling as well as the limitations for high load applications will be explained. Finally, the concluding remarks will highlight the characteristics for both anode and cathode for better choice of electrode combinations in the full batteries. Abstract : Recent progress and solutions to the challenges associated with anode nanostructures are described comprehensively. Further, possible ways to increase the energy density of LIBs and a better choice of anode materials on the basis of their resource and performance are explained. Careful tuning of structure, composition and morphology of nanostructures can develop better LIBs for future EVs.